Pemahaman ASN terhadap Core Values ASN Berakhlak di Lingkungan BPK Perwakilan Provinsi Lampung (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This paper examines civil servants' (ASN) understanding of the Core Values of Ethical Civil Service (ASN BerAKHLAK), which represent fundamental principles that civil servants must uphold in performing their duties as public servants. However, some civil servants still lack full comprehension and proper implementation of these values.The study aims to investigate and assess the level of civil servants' understanding regarding these core values within the Audit Board of the Republic of Indonesia (BPK RI), Lampung Provincial Office. Employing a quantitative descriptive method, the research reveals that 94% of BPK's Lampung Office civil servants demonstrate general awareness of the ASN BerAKHLAK values. Nevertheless, their understanding of theoretical aspects and practical implementation requires further improvement.